Pemanfaatan Praktek Kerja Lapangan (PKL) dalam Meningkatkan Keterampilan Komunikasi Mahasiswa Universitas Islam Negeri Sumatera Utara - Heny Anggreni Butar – Butar; Maulida Salsabila Purba; M. Farhan Al-Hakim; Yuda Kurniawan; Ariansyah Habibi; Hasan Sazali (CV. ITTC INDONESIA, 2025)
This study aims to analyze how Field Work Practice (PKL) plays a role in improving the communication skills of students at the State Islamic University of North Sumatra (UINSU). In this context, PKL is considered a crucial factor in developing students' communication skills. This study uses a qualitative method with data collection techniques through in-depth interviews, participatory observation, and documentation conducted in one of the villages in Indonesia. The results of the study indicate that PKL has a significant influence on improving the communication skills of UINSU students. This finding indicates that the use of PKL is very effective, especially if supported by strong mastery of verbal and nonverbal communication skills. In addition to improving technical skills, PKL also contributes to building students' self-confidence and competence in facing the challenges of the world of work in the future.